2015
DOI: 10.1016/j.ijsu.2015.05.050
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of laparoscopic versus open abdominal incisional hernia repair, with meta-analysis of randomized controlled trials

Abstract: Five randomized controlled trials (RCTs) were identified and included in the final analysis with a total number of 611 patients randomized. Three hundreds and six patients were in the laparoscopic group and 305 patients in the open repair group. The range of follow up in the studies was two months to 35 months. The recurrence rate was similar (P = 0.30), wound infection was higher in the open repair group (P < 0.001), length of hospital stay was not statistically different (P = 0.92), and finally the operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
100
2
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(116 citation statements)
references
References 36 publications
(34 reference statements)
6
100
2
8
Order By: Relevance
“…15 In our study, the operative time was shorter in open incisional hernia group however it doesn't reach significant level However, several studies have demonstrated that in experienced hands laparoscopic repair takes a similar amount of time compared to open repair. 14,15 One case of bowel injury in laparoscopic group was detected in this study versus no case in open group and this was not reach statistically significant difference, some studies reported higher incidence of bowel injury in laparoscopic group. 15 In this study one case of recurrence was detected in laparoscopic hernia group however no significant difference was detected between both groups, several studies detected no significant difference between both group as regard recurrence rate.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…15 In our study, the operative time was shorter in open incisional hernia group however it doesn't reach significant level However, several studies have demonstrated that in experienced hands laparoscopic repair takes a similar amount of time compared to open repair. 14,15 One case of bowel injury in laparoscopic group was detected in this study versus no case in open group and this was not reach statistically significant difference, some studies reported higher incidence of bowel injury in laparoscopic group. 15 In this study one case of recurrence was detected in laparoscopic hernia group however no significant difference was detected between both groups, several studies detected no significant difference between both group as regard recurrence rate.…”
Section: Discussioncontrasting
confidence: 58%
“…15 In this study one case of recurrence was detected in laparoscopic hernia group however no significant difference was detected between both groups, several studies detected no significant difference between both group as regard recurrence rate. 14,15 The main limitations of our study were small number of patient involved and it was non-randomized controlled study. We need a randomized controlled study from the developing country to detect the difference between both groups.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Las contraindicaciones relativas descritas son la presencia de adherencias extensas y firmes, hernias encarceladas con sufrimiento de asa y pérdida del domicilio con defectos de la pared abdominal de más de 10 cm. (15)(16)(17)(18) Respecto a la técnica quirúrgica, los defectos herniarios menores de tres centímetros se pueden reparar con sutura monofilamento, continua, sin necesidad de colocación de malla. Sin embargo, ante la necesidad del uso de malla por un defecto mayor se puede determinar su colocación onlay, sublay o inlay, siendo el referente la colocación tipo sublay (6) El reparo debe seguir siempre los principios de libre tensión.…”
Section: Discussionunclassified
“…Recently meta-analysis was performed on this topic but no obvious results was found yet (16). The aim of this study is to compare pain score and satisfaction rate of laparoscopic and open abdominal incisional hernia repair.…”
Section: Introductionmentioning
confidence: 98%